"Before She Was Born, I Ate Cheerios and Beer for Dinner": A Qualitative Examination of Green Parenting in Lowcountry South Carolina. Issue 4 (November 2021) - Auriffeille, Deborah McCarthy
Drawing on both social practice and social innovation research, this article analyzes 48 qualitative interviews to explore the narratives of self-described green parents who live in Lowcountry South Carolina. The interviewees talked about their motivations, challenges, and understandings of the goals and meanings of green parenting. They reported that the arrival of young children represented a new challenge but also triggered motivations to continue and often intensify green lifestyles. Parents voiced three key challenges: living "green" in a "red" state, time and financial constraints, and navigating environmental media. In parallel, they articulated three main goals: to limit their impact on earth, to live healthier lives, and to socialize their children into green living. When asked about meanings, parents stressed the overlapping importance of engaging in conscious decision-making, building connections to people and nature, and cultivating overall well-being. This study suggests that parents remain resilient in the face of multiple challenges and innovate by socializing their children to live green lifestyles.